An internal thioester in a pathogen surface protein mediates covalent host binding - Su-yin, Kan; Miriam, Walden; John M, Edwards (2015)
To cause disease and persist in a host, pathogenic and commensal microbes must adhere to tissues. Colonization and infection depend on specific molecular interactions at the host-microbe interface that involve microbial surface proteins, or adhesins. To date, adhesins are only known to bind to host receptors non-covalently. Here we show that the streptococcal surface protein SfbI mediates covalent interaction with the host protein fibrinogen using an unusual internal thioester bond as a ‘chemical harpoon’. This cross-linking reaction allows bacterial attachment to fibrin and SfbI binding to human cells in a model of inflammation. Thioester-containing domains are unexpectedly prevalent in Gram-positive bacteria, including many clinically relevant pathogens. Our findings support bacterial-encoded covalent binding as a new molecular principle in host-microbe interactions. This represents an as yet unexploited target to treat bacterial infection and may also offer novel opportunities for engineering beneficial interactions.